Chinese students’ perceptions of women in management: will it be easier? - Frank, Ellen J (Women in Management Review, 2001)
An attitude survey was conducted with 72 management majors attending a prestigious business university in Beijing, China. The results indicate that there is still a significant “glass ceiling” effect to accepting women as they climb up the management hierarchy. The group estimated that it would take at least 32 years before equality would be reached. Women were less likely to prefer to work for a woman than for male subjects. Women were described as more incompetent, slower, weaker, more a follower-than-a-leader, more lenient, more democratic, less active, and more friendly than male managers. Women were significantly more in agreement with the idea of being both a professional and a wife. The results reflect a similar attitudinal position to US women. The conclusion is that it will not be easier for Chinese women to succeed than it is for women in theUSA. © 2001, MCB UP Limited
6 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/077-606-789-075-245 tex.type: [object Object]
Keywords: Attitudes; China; Management; Managers; Perception; Women; dept.mgt